2009
DOI: 10.1002/jemt.20771
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin/tyrosine‐phosphorylated cortactin interaction with connexin 43 in mouse seminiferous tubules

Abstract: Deletion of the cortactin gene leads to male infertility. Considering that cortactin is an actin filament (F-actin)-binding protein associated with intercellular junctions, we measured changes in the expression and distribution of cortactin and tyrosine phosphorylated cortactin (P-cortactin) in the seminiferous epithelium of developing and adult mice to address the physiological significance of cortactin to germ cell differentiation. Cortactin was expressed in neonatal and developing Sertoli cells. Cortactin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…Our observation of a high Cx43 gene expression was matched with Cx43 protein levels that decreased from 210 -270 days and from December-March in normal mink tubules confirms our earlier report of total Cx43 levels falling with adulthood in mouse tubules (84). This decrease in Cx43 protein levels despite elevated Cx43 mRNA levels signifies that either lesser Cx43 protein amounts were synthesized or greater amounts were lost through degradation or through other means during these periods.…”
Section: Cx43 Expression and Phosphorylation In Normal Vs Orchitic Minksupporting
confidence: 90%
“…Our observation of a high Cx43 gene expression was matched with Cx43 protein levels that decreased from 210 -270 days and from December-March in normal mink tubules confirms our earlier report of total Cx43 levels falling with adulthood in mouse tubules (84). This decrease in Cx43 protein levels despite elevated Cx43 mRNA levels signifies that either lesser Cx43 protein amounts were synthesized or greater amounts were lost through degradation or through other means during these periods.…”
Section: Cx43 Expression and Phosphorylation In Normal Vs Orchitic Minksupporting
confidence: 90%
“…It has been previously reported by our group and others that actin-binding proteins provide a physical linkage between Cx43 and the cortical cytoskeleton and that these interactions are required for maintaining functional Cx43-formed gap junctions in differentiating myoblasts [6,58]. Among the different proteins interacting with connexins are the ZO proteins, vinculin, ezrin, a-actin and cortactin [6,47,58]. In this study we showed that TRPC1 channels could regulate the remodeling of a specific pool of Cx43 protein, likely through the stabilization and coordination of its interaction with cortactin.…”
Section: Discussionmentioning
confidence: 93%
“…It consists of F-actin [ID: T2-193], Sak57 an ortholog of keratin 5 [ID: T2-194], myosin , an actin based motor protein, and cortactin (Kierszenbaum et al, 2008). Several reports, however, have shown that only Sertoli cells express cortactin and that it is localizes to these cells in the developing and adult testis (Anahara et al, 2006;Chapin et al, 2001;Kai et al, 2004;Vitale et al, 2009), in contrast to claims that P-cortactin occupies the subacrosomal space of round spermatids (Kierszenbaum et al, 2008). RAB27A and RAB27B are present in the Golgi apparatus and marginal rim of the acroplaxome region.…”
Section: Microscopy Research and Techniquementioning
confidence: 99%